Combining Rule-based and Statistical Methods for Named Entity Recognition in Portuguese - Ferreira, Eduardo; Balsa, João; Branco, António (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2007: Anais do V Workshop em Tecnologia da Informação e da Linguagem Humana, 2007)
We present and discuss a tool for the recognition of expressions for named entities in Portuguese that resorts to a rule-based approach when dealing with numbers, measures, time and addresses, and uses a hybrid approach when dealing with names. The expressions for named entities are delimited and semantically classified by a XML-like markup. Evaluation results are presented.